Active Mobility and Blood Pressure: Roles of Black Carbon and Physical Activity. (June 2017) - Avila-Palencia, Ione; Laeremans, Michelle; Pablo Orjuela, Juan; Carrasco-Turigas, Glòria; Dons, Evi; Cole-Hunter, Tom; Int Panis, Luc; de Nazelle, Audrey; Nieuwenhuijsen, Mark
Abstract : Background: Active mobility (ie walking and cycling) has been associated with health benefits like increasing levels of physical activity and reduction of cardiovascular risk in the general population. However, increased inhalation rate during physical activity may result in increased inhaled dose of traffic-related air pollutants. short-term exposure to traffic-related air pollutants has been associated with adverse cardiovascular outcomes like increasing blood pressure. The current study evaluates the association between active mobility patterns and blood pressure, and also if the exposure to black carbon and levels of physical activity are mediators of this association. Methods: A panel study was performed in three European cities (Antwerp, Barcelona, and London) with 119 healthy adults (approximately 40 participants/city) who completed three 7-day measurement periods in winter, summer, and mid-season. Between February 2015 and March 2016 they wore sensors to measure the exposure to black carbon (i.e. a marker of traffic-related air pollutants) and to monitor their physical activity levels. blood pressure was measured three times during each measurement period: at the beginning (day 0), middle (day 4), and end (day 7). On these days, participants also completed a questionnaire about their personal characteristics and lifestyle behaviours. Multilevel regression models will be used to evaluate the association between active mobility and blood pressure, and Baron and Kenny's framework will be followed to establish the mediation roles. All models will be adjusted for potential confounders. Results: The analyses for this study are ongoing. The current sample had a fairly equal distribution of sexes (55% females) and the mean age was 35 ± 10 years. The majority of participants were Caucasian (94%) and had high education degrees (89%). The sample was fairly active with a median (Inter-quartile range) moderate-to-vigorous physical activity of 71 (49-111) min/day measured by an accelerometer. Mean black carbon exposure over all sample in coinciding time periods was 1636 ± 673 ng/m³. The mean black carbon exposure increased with higher levels of physical activity. We expect to find an association between active mobility patterns and lower BP. We also expect to find indications for mediation of this association by black carbon exposure and physical activity levels. Conclusions: The increased levels of physical activity through active mobility could attenuate the effects of black carbon exposure in blood pressure.